Hydrogen-induced structural change in Ni90Al10 metallic glass - Park, Kyoung-Won; Shibutani, Yoji; Fleury, Eric (ELSEVIER SCIENCE SA, 2011)
Ni90Al10 amorphous membranes were prepared by means of molecular dynamics ( MD) simulation technique with the aim of investigating the structural evolution induced by hydrogen with respect to hydrogen concentration. The short-range ordered (SRO) structures of the as-cast model sample and the structural change by hydrogen charging were analyzed using Voronoi tessellation method. This study indicates that prism and prism-like structures with low coordination number are generated, while intrinsically stable SRO structures in the amorphous membrane annihilate upon hydrogen charging. We discussed the relationship between these local atomic changes and the structural stability which was evaluated from the potential energy change point of view. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ZR AMORPHOUS-ALLOYS; PERMEATION PROPERTIES; MECHANICAL-PROPERTIES; LATTICE-DEFECTS; TI; MEMBRANE; SEPARATION; NICKEL